2019
DOI: 10.1137/17m1154205
|View full text |Cite
|
Sign up to set email alerts
|

A Geometrical Method for Low-Dimensional Representations of Simulations

Abstract: We propose a new data analysis approach for the efficient post-processing of bundles of finite element data from numerical simulations. The approach is based on the mathematical principles of symmetry. We consider the case where simulations of an industrial product are contained in the space of surface meshes embedded in R 3 . Furthermore, we assume that distance preserving transformations exist, albeit unknown, which map simulation to simulation. In this setting, a discrete Laplace-Beltrami operator can be co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In the engineering domain, it has been shown that spectral mesh representations using the Laplace-Beltrami operator are an adequate choice for representing several deformations in a compact way [Garcke and Iza-Teran, 2017, Iza-Teran, 2016, Iza-Teran and Garcke, 2019. Here, an approach has been proposed that uses the decomposition of one Laplace-Beltrami operator for a series of deformations, which are assumed to be isometric to a base shape.…”
Section: Spectral Mesh Process-ing In the Engineering Domainmentioning
confidence: 99%
See 4 more Smart Citations
“…In the engineering domain, it has been shown that spectral mesh representations using the Laplace-Beltrami operator are an adequate choice for representing several deformations in a compact way [Garcke and Iza-Teran, 2017, Iza-Teran, 2016, Iza-Teran and Garcke, 2019. Here, an approach has been proposed that uses the decomposition of one Laplace-Beltrami operator for a series of deformations, which are assumed to be isometric to a base shape.…”
Section: Spectral Mesh Process-ing In the Engineering Domainmentioning
confidence: 99%
“…Spectral coefficients obtained by projecting several mesh deformations in x-, yand z-directions into a common eigenbasis are used as a dimensionality reduction and visualization technique for large sets of deformed shapes resulting from crash simulations. It has also been proposed that certain eigenvectors can be interpreted as specific geometric operations on the shape, e.g., a translation in the Euclidean space [Iza-Teran and Garcke, 2019]. Furthermore, the presented approach allows to handle arbitrary discrete functions defined on the mesh, so that additional functional properties of a part, such as plastic strain or stress, may be represented in the spectral domain.…”
Section: Spectral Mesh Process-ing In the Engineering Domainmentioning
confidence: 99%
See 3 more Smart Citations